ANALISIS KESALAHAN MAHASISWA DALAM MEMBUAT SKRIPSI - Sudarto, Sudarto (Jurnal Cakrawala Ilmiah, 2024)
This research is a library research which aims to find out the students' mistakes in writing their thesis reports in relation to the validity and reliability of the research instruments. The research object is the 15 copies of student theses for 2016, 2017, 2021, 2022 and 2023. The data collection technique used is to directly examine the data source, namely the student theses. The research instrument used was a document recording sheet. The data analysis technique used is narrative descriptive and quantitative descriptive data analysis techniques. Results and conclusions: the mistakes were made by the students (thesis writers/makers) in conducting the thesis research or writing the thesis regarding instrument validation and reliability include: the students/thesis makers not carrying out the empirical validation and not carrying out the reliabilization, validating research instruments (content/surface validation/ construct), but it is not clear in what terms the instrument was validated and in the validation sheet it is not clear in what terms (on what criteria) the validator gives a score of 1, 2, 3, and 4 on the items to be validated, the improvements that have been made based on validator suggestions/input are not included in the thesis, improvements that have been made based on the validator's suggestions/input are not included in the thesis, validating learning tools that should not be necessary, and not validating content/surface/construct instruments (not including evidence) evidence related to instrument validation). The biggest mistake students/thesis makers namely they were not implementing the empirical validity and reliability of the instruments